Recent Advances in the Diagnosis and Treatment of Halitosis - Alison, Leedwin Kalyana; Cuan, How Kim; Halim, Susanna (Journal of Science and Science Education, 2025)
Halitosis is commonly defined as an unpleasant or offensive odour that is emitted from the oral cavity. For many individuals with halitosis, the condition leads to discomfort and affects their social interactions and everday activities. Additionally, bad breath may indicate an underlying health issue. Identifiying the contributing factors and causes of halitosis can help ensure effective treatment and management of the condition. This review aims to improve general awareness of halitosis, with a particular focus on intra oral halitosis and also to provide practitioners with the latest information on the causes of halitosis, hightlighting effective approaches for prevention and treatment. Regular daily oral care including brushing with toothpaste, flossing and using antimicrobial agents, effectively reduces the number of microorganisms responsible for bad breath